Аналіз існуючих підходів і методів забезпечення безпеки інфраструктури у хмарному середовищі - Красюкова, В. В. (ХНУРЕ, 2024)
The use of cloud environments is an essential part of working with information technologies. The use of cloud technologies requires thorough security measures. Key methods include multifactor authentication, limiting user access to the necessary minimum, network protection, and data encryption. Recommendations include creating network tiers, securing networks, using certificates, and encrypting traffic. Traffic filtering and monitoring, automated response to threats, auditing, and adherence to standards such as ISO/IEC 27001 are crucial for ensuring a high level of security and trust in cloud environments.
Keywords: хмарне середовище; безпека інфраструктури у хмарному середовищі